The Impact of Andesite Mining at PT Atika Tunggal Mandiri (ATUM) on the Social, Economic, and Environmental Conditions of the Community in Nagari Manggilang, Pangkalan Koto Baru District - Dinda Isnania; Alexander Syam; Zamhar Bakri (Cv. Kilau Rashdan Publishing, 2026)
This research aims to analyze the impact of andesite mining conducted by PT. Atika Tunggal Mandiri (ATUM) on the social, economic, and environmental conditions of the community in Nagari Manggilang, Pangkalan Koto Baru District. The type of research used is qualitative with a descriptive method. The informants in this study consisted of 20 people, including the Wali Nagari of Manggilang, the owners of the andesite mine, the andesite mine workers, and the local community. The data types required are primary and secondary data, collected using purposive sampling techniques. The data were gathered through observation, interviews, and documentation. The data analysis stages included Data Reduction, Data Presentation, and Conclusion Drawing. The results indicate that, socially, mining activities affect community interaction patterns, with changes in social structure due to labor migration and increased social tensions. Economically, andesite mining provides job opportunities and increases income for some residents, but it also creates economic disparities within the community. The environmental impacts found include ecosystem damage and increased air and water pollution, which affect the quality of life of the surrounding residents. This study suggests that the government and mining companies should pay more attention to sustainability aspects and the balance between economic growth and environmental conservation, while also ensuring the social welfare of the community around the mining area.